Graphene A Wonder Material for Scientists and Engineers - Ikram, Mujtaba; Maqsood, Asghari; Bashir, Aneeqa (IntechOpen, 2023)
Graphene is considered as a miracle material for scientists and engineers owing to its outstanding physical properties. Graphene and its nanocomposites are promising multifunctional materials with improved tensile strength and elastic modulus. graphene nanocomposites may have a wide range of potential applications due to their outstanding properties and the low cost of graphene. Because graphene composites have a controllable porous structure, a large surface area, high conductivity, high-temperature stability, excellent anti-corrosion properties, and composite compatibility, they can be used in energy storage as electrocatalysts, electro-conductive additives, intercalation hosts, and an ideal substrate for active materials. Shortly, graphene will be a base for the next generation's scientific revolution.